Staatenkunde als Weltbeschreibung - Reddemann, Lukas, (Early Modern History and Modern History E-Books Online, Collection 2024., 2024)
This study offers the first large-scale study of the earliest and most notable early modern book series of state descriptions, the 'Republics'. Printed in Leiden and Amsterdam in the 1620s and 30s, they evolved into foundational works of early modern statistics. By first tracing the volumes' circulation and presence in book collections and libraries in the 17th century, this study offers fresh insights into their diverse readerships as well as their prominent role in the early modern book market. It then provides insights into their various academic purposes and their textual, intellectual, and political traditions through selected case studies on the Dutch Republic, the Spanish Empire, and Safavid Persia.